ÁDÁM SZABÓ, DOMNA ET DOMNUS. CONTRIBUTIONS TO THE CULT-HISTORY OF THE ’DANUBIAN-RIDERS’ RELIGION - Csaba Szabó (Journal of Ancient History and Archaeology)
ÁDÁM SZABÓ, DOMNA ET DOMNUS. CONTRIBUTIONS TO THE CULT-HISTORY OF THE ’DANUBIAN-RIDERS’ RELIGION, Hungarian Polis Studies 25, Phoibos Verlag, Wien, 156.p. ISBN 978-3-85161-179-3.